PASAR, WADAH STRATEGIS ZAKAT DAN AMAL SOSIAL - Nasir, Amin (UIN Sunan Kudus, 2017)
Zakah is one of the characteristics of the Islamic economic system, because zakah is one of the implementation of the principle of justice in the Islamic economic system. Trade is one form of legal business. The predominantly Muslim village of Mejobo has considerable potential associated with zakat, where the mejobo village has a prominent market commodity in the south of the southern part of the potential Brayung market in which a total of approximately 1000 traders in the Mejobo Village market. Materially the traders gain prosperity through two things: capital turnover and reasonable trade margin. However, in reality the merchants are distributing their zakah directly to mustahiq without going through zakah institution in the form of money every close to Eid al-Fitr. In addition, they also channel their zakah to a person who is not assigned as an amilin or zakah officer but to a person who is trusted to distribute. It is unfortunate if this large potential is not touched optimally by the zakah amil institutions in both the private and government. So it can be ascertained that the prospect of Brayung Desa Mejobo market must be developed maximally so that in addition to the obligation of Muslims to pay zakah, it also affects the social good and reduces the burden of the government.